Integration of Islamic Values and Lawrence Kohlberg's Theory in The Moral Development of Students - Auliya', Hilyatul; Bakar, M. Yunus Abu (Institut Islam Mamba'ul 'Ulum Surakarta, 2026)
This study aims to examine the integration between Islamic moral values and Kohlberg’s theory of moral development in order to understand the process of students’ moral formation within Islamic education. The research employed a qualitative approach using literature research, analyzing primary and secondary sources related to Islamic ethics and moral development theory. The findings indicate that Islamic moral values such as justice ('adl), honesty (sidq), and responsibility (amanah) can be conceptually aligned with the stages of moral development proposed by Kohlberg. This integration provides a more comprehensive framework for moral education that combines cognitive moral reasoning with spiritual and ethical principles derived from Islamic teachings. The study suggests that Islamic moral education should not only focus on the transmission of moral norms but also encourage reflective ethical reasoning and the internalization of spiritual values in students’ character formation.